Study of InN surface by high resolution electron energy loss spectroscopy (HREELS ) - Acharya, Ananta R.; Thoms, Brian D. (Himalayan Physics, 2011)
Understanding the surface structure and termination of semiconductor thin films during epitaxial growth is critical since it affects the structural, interfacial and electronic properties of epilayers and device structures. The structural properties and surface bonding configuration of InN layers grown by high pressure chemical vapor deposition (HPCVD) have been characterized using high resolution electron energy loss spectroscopy (HREELS). The HREELS analysis of these InN layers shows that the surface is predominantly terminated with NH2 species. This is in contrast to previous work on HPCVD-grown InN layers, which showed only NH species on the nitrogen terminated surface. The presence of NH2 related modes of vibration is the indication of the orientation of the surface other than c-plane. Key words: HREELS; Indium nitride; NH2 The Himalayan Physics Vol.2, No.2, May, 2011 Page: 35-37 Uploaded Date: 1 August, 2011